Spatial Decision Assistance of Watershed Sedimentation (SDAS): Development and Application - R. Poerbandono; Agung B. Harto; Miga M. Julian (Journal of Engineering and Technological Sciences, 2014)
This paper discusses the development and application of a spatial tool for erosion modeling named Spatial Decision Assistance of Watershed Sedimentation (SDAS). SDAS computes export (yield) of sediment from watershed as product of erosion rate and sediment delivery ratio (SDR). The erosion rate is calculated for each raster grid according to a digital elevation model, soil, rain fall depth, and land cover data using the Universal Soil Loss Equation. SDR calculation is carried out for each spatial unit. A spatial unit is the smallest sub-watershed considered in the model and generated according to the TauDEM algorithm. The size of one spatial unit is assigned by the user as the minimum number of raster grids. SDR is inversely proportional to sediment resident time and controlled by rainfall, slope, soil, and land cover. Application of SDAS is demonstrated in this paper by simulating the spatial distribution of the annual sediment yield across the Citarum watershed in the northwest of Java, Indonesia. SDAS calibration was carried out based on sediment discharge observations from the upper catchment. We considered factors for hillslope flow depth and for actual and effective rainfall duration to fit the computed sediment yield to the observed sediment discharge. The computed sediment yield agreed with the observation data with a 7% mean relative accuracy.